Drought and Salinity Stress Responses and Microbe-Induced Tolerance in Plants - Ma, Ying; Dias, Maria Celeste; Freitas, Helena (Frontiers in plant science, 2020)
Drought and salinity are among the most important environmental factors that hampered agricultural productivity worldwide. Both stresses can induce several morphological, physiological, biochemical, and metabolic alterations through various mechanisms, eventually influencing plant growth, development, and productivity. The responses of plants to these stress conditions are highly complex and depend on other factors, such as the species and genotype, plant age and size, the rate of progression as well as the intensity and duration of the stresses. These factors have a strong effect on plant response and define whether mitigation processes related to acclimation will occur or not. In this review, we summarize how drought and salinity extensively affect plant growth in agriculture ecosystems. In particular, we focus on the morphological, physiological, biochemical, and metabolic responses of plants to these stresses. Moreover, we discuss mechanisms underlying plant-microbe interactions that confer abiotic stress tolerance.